Impact of pulmonary hypertension and right ventricular function on outcomes of isolated tricuspid valve surgeryCentral MessagePerspective - Salah E. Altarabsheh, MD; Juan A. Crestanello, MD; Nishant Saran, MD; Richard C. Daly, MD; Joseph A. Dearani, MD; Kevin L. Greason, MD; John M. Stulak, MD; Austin Todd, MS; Phillip G. Rowse, MD; Arman Arghami, MD; Gabor Bagameri, MD; Mauricio A. Villavicencio, MD; et al. (JTCVS Open)
Objective: To evaluate the impact of pulmonary hypertension and right ventricular dysfunction on outcomes of isolated tricuspid valve surgery. Methods: From 2004 to 2022, 298 patients (age 71.0 ± years, 59.4% female) underwent isolated tricuspid valve surgery. Pulmonary hypertension was defined as right ventricular systolic pressure ≥50 mm Hg, and right ventricular dysfunction as right ventricular fractional area change <32% on preoperative transthoracic echocardiogram. Patients were stratified into 4 groups: group I: No pulmonary hypertension or right ventricular dysfunction (n = 199), group II: pulmonary hypertension without right ventricular dysfunction (n = 45), group III: right ventricular dysfunction without pulmonary hypertension (n = 43), and group IV: pulmonary hypertension and right ventricular dysfunction (n = 11). Uni- and multivariable analyses were performed to evaluate association of pulmonary hypertension and right ventricular function with outcomes. Results: Tricuspid valve replacement was performed in 218 (73.2%) and repair in 80 (26.8%) patients. Operative mortality was 4.7%, similar for reoperations (5.2%) and primary procedures (4.5%) (P = .907). Median follow-up was 5.4 (interquartile range, 2.3-12.5) years, survival was 74.4%, 48.4%, 39.8%, and 67.3% in groups I-IV, respectively (P < .0001). Multivariable analysis identified pulmonary hypertension (hazard ratio, 2.9; 1.83-4.62, P < .001) and right ventricular dysfunction (hazard ratio, 2.83; 1.76-4.56, P < .001) as independent predictors of greater long-term all-cause mortality, in addition to older age (P < .001) and severe chronic lung disease (P < .001). Conclusions: Among patients who underwent isolated tricuspid valve surgery, presence of pulmonary hypertension or right ventricular dysfunction at baseline is linked to greater long-term mortality.